Activities that Encourage Nationalistic Insight among Santriwati of Darul Hijrah Pesantren Putri Cindai Alus Martapura - Rahmaniah Rahmaniah; Mutiani Mutiani; M. Ridha Ilhami; Sigit Triyono; Syarifuddin Syarifuddin (The Innovation of Social Studies Journal, 2025)
National insight is an important aspect in building awareness as a citizen who has a responsibility for the progress of the nation and is a part that must be understood, including santriwati. The cultivation of nationalistic insight towards santriwati in Islamic boarding schools, namely at the Darul Hijrah Putri Islamic Boarding School, which is not only limited to the theory taught in the subjects but also by direct practice. The purpose of the research is to describe and illustrate the national insight of santriwati in the Darul Hijrah Putri Islamic Boarding School. Qualitative approach and descriptive method are used in this research where data is obtained directly from female santri and ustadz/ustadzah with a total of 11 informants. The data collection techniques used include observation, interviews, and documentation. As for the data analysis technique, it is carried out through the stages of data reduction, data presentation, and inference. Data validity is confirmed by triangulation of sources, techniques, and time. The results of the study illustrate; Nationalistic insight at Darul Hijrah Putri Islamic Boarding School is carried out through the implementation of learning activities, commemoration of National Holidays such as National Santri Day on October 22 and Indonesian Independence Day on August 17 each year, extracurricular activities and organizational activities (OSDA), and weekly daily routines that emphasize the values of discipline, responsibility and solidarity. In conclusion, Pondok Pesantren Darul Hijrah Putri Cindai Alus Martapura has succeeded in creating an environment that supports the development of nationalism among female santri. Through various planned and systematic activities, santriwati are not only equipped with knowledge, but also with attitudes. The nationalistic insight of santriwati of Darul Hijrah Putri Islamic Boarding School is realized through the implementation of various activities that can strengthen the sense of love for the country and individual awareness as responsible citizens in creating a generation that is ready to contribute positively to society and the nation.